Assessing the Potential Role of Pigs in the Epidemiology of Ebola Virus in Uganda. Issue 2 (27th August 2015) - Atherstone, C.; Smith, E.; Ochungo, P.; Roesel, K.; Grace, D.
Summary: Uganda has experienced 4 Ebola outbreaks since the discovery of the virus. Recent epidemiological work has shown pigs are hosts for Ebola viruses. Due to their high reproduction rates, rapid weight gain, potential to provide quick financial returns and rising demand for pork, pig production in Uganda has undergone massive expansion. The combination of pork sector growth supported by development programmes and Ebola virus risk prompted a foresight exercise using desk, interview and spatial methods. The study found that the lack of serological evidence for specific reservoir species, the number of human index cases unable to account for their source of infection, domestic pig habitat overlap with potential Ebola virus zoonotic host environments, reported interactions at the human–pig–wildlife interface that could support transmission, fever in pigs as a commonly reported problem by pig farmers and temporal correlation of outbreaks with peak pork consumption periods warrants further research into potential zoonotic transmission in Uganda from pigs.